Aproximación temática a la investigación sobre la interculturalidad: un análisis de copalabras a partir de mapas de densidad y proximidad en artículos de investigación indexados en Web of Science en los últimos tres años (2021)
This article aims to identify the subject areas in the production of scientific knowledge related to interculturality. For this purpose, the co-word analysis of research articles published in the last three years (2020, 2019 and 2018) was used, through a process of retrieval of bibliographic references in the Web of Science databases. In the process, the term intercultur* was used to obtain a set of references from which a density map was obtained for each year using the VOSviewer software. Subsequently, a retrieval process of references using the term interculturality” in the Web of Science Core Collection database was carried out to analyze the production indicator by country and to obtain a proximity map. In the density maps comparative analysis, it was found that the area of education, mainly in learning a foreign language and cultural exchange, is of greater prominence and stability over time. Furthermore, through the production indicator, it was possible to demonstrate the leadership of Latin America and Spanish-speaking countries in the production of research articles related with the keyword interculturality. Finally, two additional fields of knowledge were identified from the analysis of the proximity map, which were classified in the categories “coloniality and territory” and “ethnicities and inequality”.